2020
DOI: 10.1080/09064710.2020.1712470
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and profitability of maize-legume cropping systems under conservation agriculture among smallholder farmers in Malawi

Abstract: A study was conducted from 2014 to 2017 in Malawi to elucidate the short-term effects of maizelegume intercropping and rotation systems under conservation agriculture (CA) and conventional tillage (CT) on crop productivity and profitability. Twelve farmers hosted on-farm trials per district, in three districts, with each farmer having six plots. The design of the study was randomised complete block design arranged in a split plot fashion with tillage as main plot and cropping systems as subplots, with each far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Maize (Zea mays L.)-legume intercrops can also provide protein-rich food in low-input agricultural systems, bringing overall benefits to soil fertility conservation, pest management, and animal feed [16,17]. In Malawi, a three-year study was carried out to compare the performance of maize-legume intercropping under conservation agriculture and conventional tillage on twelve farms [18]. Legume production varied with species and farm, but maize production was higher in the second (by 1.4 t ha −1 ) and third (by 3.2 t ha −1 ) growing seasons in conservation agriculture compared to conventional cultivation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maize (Zea mays L.)-legume intercrops can also provide protein-rich food in low-input agricultural systems, bringing overall benefits to soil fertility conservation, pest management, and animal feed [16,17]. In Malawi, a three-year study was carried out to compare the performance of maize-legume intercropping under conservation agriculture and conventional tillage on twelve farms [18]. Legume production varied with species and farm, but maize production was higher in the second (by 1.4 t ha −1 ) and third (by 3.2 t ha −1 ) growing seasons in conservation agriculture compared to conventional cultivation.…”
Section: Introductionmentioning
confidence: 99%
“…Estimating the land equivalent ratio (LER) in intercrops also leads to an understanding of the interactions affecting yields. LER is defined as the relative land area required as sole crops to produce the same yields as intercropping [20] and has been successively used in many studies, providing valuable information for the management of intercrops [14,18,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…In a similar GM analysis Kabambe et al (2018) also reported that GM of maize was positive for yields and prices of 4,000 kg ha -1 and US$0.27 kg -1 respectively. Recently, Ngwira et al (2020) reported GMs of US$1000-1800 from on-farm maize trails in Malawi.…”
Section: Gross Margins Value Cost Ration and Benefit-cost Ratiomentioning
confidence: 99%
“…Similarly, green gram (Vigna radiata L.) and black gram (Vigna mungo L.) may impart sustainability to maize-legume intercropping system by enhancing land use efficacy attained through higher utilization efficiency of farm applied inputs. However, optimization of intercropping system may potentially reduce the degree of inter and intra species competition and boost the added benefits offered by cereal-legume intercropping systems [9][10][11][12][13], which continues to remain an unexplored aspect under irrigated conditions of semi-arid environment. This is of the utmost importance as numerous types of species-specific mechanisms alter the physiological response of intercrops and directly determine the extent of added advantage offered by intercropping system.…”
Section: Introductionmentioning
confidence: 99%